Morphometric Characterization and Genetic Distance among Four Breeds of Rabbit (Oryctolagus cuniculus) - Setiaji, A; Sutopo, Sutopo; Kurnianto, E (ANIMAL PRODUCTION, 2012)
An experiment was conducted to elucidate performance of body measurements and to estimate genetic distance among four breeds of rabbit, those were Flamish Giant, English Spot, Angora and Rex. Material of the experiment was 352 heads of four breeds of rabbit originating from three districts of Jambu, Sumowono and Ungaran in Semarang Regency-Central Java. Experiment material was determined by purposive sampling method on the basis of population density. Parameters observed were 1) head length, 2) head width , 3) ear length, 4) ear width, 5) chest circumference, 6) chest depth, 7) chest width, 8) humerus length, 9) radius-ulna length, 10) tibia length, 11) femoris length, 12) body length, and 13) hip width. SAS package program was used to analyze data. Phenogram tree was constructed using MEGA 5. Results showed that there was no difference on the morphometric performance between sex within breed with exception in Flamish Giant. Rabbits in Jambu district tended to have similarity in body measurement with those in Sumowono, but differed from rabbits in Ungaran. Cumulative contribution ratio from the first principal component (PC1) to the third principal component (PC3) was 83.6%. The genetically closeness was shown among Flamish Giant, English Spot and Angora, while Rex had a much different character.Â Keywords: morphometric, genetic distance, rabbitÂ Animal Production 14(2):92-98Â